Pengembangan media pembelajaran Al-Quran Hadis berbasis Prezi - Firli, Fatihana; Milla, Sri Nurul; Hidayat, Muhammad Faishal (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2025)
Learning Al-Qur'an Hadith needs to be made interesting so that students are more enthusiastic about learning, and Prezi media can help because of its attractive and interactive appearance. This study aims to develop Prezi-based learning media and test its feasibility level in the subject of Al-Qur'an Hadith material “Halal and Good Food”. The method used in this research is the Research and Development (R&D) method with the 4D model which consists of 4 stages, namely define, design, develop, and disseminate. The research was conducted on grade XI students of MAN 2 Bogor City. The validation results obtained an average score of 91.3% and the product trial results obtained an average score of 87.3%. Both are included in the “Very Valid” category, indicating that Prezi learning media for the subject of Al-Qur'an Hadith material “Halal and Good Food” is suitable for use. Abstrak Pembelajaran Al-Qur’an Hadis perlu dibuat menarik agar siswa lebih semangat belajar, dan media Prezi dapat membantu karena tampilannya yang menarik dan interaktif. Penelitian ini bertujuan untuk melakukan pengembangan media pembelajaran berbasis Prezi dan menguji tingkat kelayakannya pada mata pelajaran Al-Qur’an Hadis materi “Makanan Halal dan Baik”. Metode yang digunakan dalam penelitian ini adalah metode Research and Development (R&D) dengan model 4D yang terdiri dari 4 tahapan yaitu define (pendefinisian), design (perancangan), develop (pengembangan), dan disseminate (penyebaran). Penelitian dilakukan pada siswa kelas XI MAN 2 Kota Bogor. Hasil validasi diperoleh rata-rata skor 91,3% dan hasil uji coba produk diperoleh rata-rata skor 87,3%. Keduanya termasuk ke dalam kategori “Sangat Valid” sehingga menunjukkan bahwa media pembelajaran Prezi mata pelajaran Al-Qur’an Hadis materi “Makanan Halal dan Baik” layak digunakan.